Outcomes of Liver Resections after Liver Transplantation at a High-Volume Hepatobiliary Center - Pohl, Julian M. O. (J Clin Med, 2020)
Although more than one million liver transplantations have been carried out worldwide, the literature on liver resections in transplanted livers is scarce. We herein report a total number of fourteen patients, who underwent liver resection after liver transplantation (LT) between September 2004 and 2017. Hepatocellular carcinomas and biliary tree pathologies were the predominant indications for liver resection (n = 5 each); other indications were abscesses (n = 2), post-transplant lymphoproliferative disease (n = 1) and one benign tumor. Liver resection was performed at a median of 120 months (interquartile range (IQR): 56.5–199.25) after LT with a preoperative Model for End-Stage Liver Disease (MELD) score of 11 (IQR: 6.75–21). Severe complications greater than Clavien–Dindo Grade III occurred in 5 out of 14 patients (36%). We compared liver resection patients, who had a treatment option of retransplantation (ReLT), with actual ReLTs (excluding early graft failure or rejection, n = 44). Bearing in mind that late ReLT was carried out at a median of 117 months after first transplantation and a median of MELD of 32 (IQR: 17.5–37); three-year survival following liver resection after LT was similar to late ReLT (50.0% vs. 59.1%; p = 0.733). Compared to ReLT, liver resection after LT is a rare surgical procedure with significantly shorter hospital (mean 25, IQR: 8.75–49; p = 0.034) and ICU stays (mean 2, IQR: 1–8; p < 0.001), acceptable complications and survival rates.